THE REGIONALISATION OF BLOCKCHAIN TECHNOLOGY AS ASEAN CYBERSECURITY STRATEGY AGAINST TERRORIST FINANCING THROUGH CRYPTOCURRENCY - Ningsih, Sabda; Syuryansyah, Syuryansyah (Global: Jurnal Politik Internasional, 2026)
Through this study, the authors question how the prospects for ASEAN regionalisation relate to the development of blockchain technology as a cybersecurity medium. Based on previous research, ASEAN is facing a problem of terrorism, which is difficult to handle over time. The finding further exacerbates the fact that transnational terrorist groups have begun to use virtual currency as one of their strategies for funding organisations. Meanwhile, Southeast Asia, according to results of several surveys, includes areas with high numbers of cryptocurrency users, making it a target for blockchain technology companies to establish main offices. Within the framework of ASEAN regionalism, the author argues that ASEAN blockchain technology can be used to address terrorist financing through cryptocurrencies, but is hindered by the principle of non-interference. Prioritising each other's sovereignty has left ASEAN unprepared to face the cryptocurrency fever, as each member country has different views and interests regarding virtual currencies. This can be seen in the non-uniformity of regulations across ASEAN member countries, and there are no specific,  binding rules from the regional organisation regarding the use of cryptocurrencies. As a result, the use of blockchain technology by ASEAN member countries is adjusted to their national interests. Then there is no initiative from ASEAN members to bring this issue into the regional realm; in fact, what is driving it is the private sector and blockchain users in Southeast Asia.